Determinants of Purchase Decisions for Physical K-pop Albums: Evidence from Starship Entertainment Consumers in Indonesia - Muhammad Sa’ad Trisnawijaya; Brian Jesse Jirajaya; Richard Efrem Yosal; Nicolas Tijang; Ian Thomas Sumilat; Muchtar Muchtar (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to analyze the influence of Service Quality, Brand Image, Promotion, and Product Quality on Customer Satisfaction and their implications for Purchase Decisions related to physical K-pop albums associated with Starship Entertainment artists. Research Method: This study employed a quantitative explanatory approach using survey data collected from 114 respondents in Indonesia who had previously purchased physical albums from Starship Entertainment artists. Respondents were selected using purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software, including measurement and structural model evaluation. Results and Discussion: The findings indicate that Service Quality, Brand Image, Promotion, and Product Quality positively influence Customer Satisfaction. Furthermore, Customer Satisfaction positively influences Purchase Decisions for physical K-pop albums. The results suggest that consumers’ evaluations of product quality, promotional communication, service performance, and agency reputation contribute to purchasing behavior in the entertainment industry. Implications: The findings provide practical insights for entertainment agencies regarding the importance of maintaining product quality, effective promotional communication, service reliability, and positive brand reputation to strengthen consumer purchasing decisions. Originality: This study develops a structured marketing-based model that examines Purchase Decisions in the context of physical K-pop album consumption using measurable consumer behavior constructs.